2021
DOI: 10.26425/2309-3633-2021-9-1-112-126
|View full text |Cite
|
Sign up to set email alerts
|

Omnichannel marketing and beacon technologies: experience and prospects in Europe

Abstract: The article presents the main results obtained from the use of Omnichannel marketing strategy and Beacon technologies in the field of European trade, determines by the difference between multichannel and omnichannel marketing strategies. For the development of the main directions of digital technologies in the field of marketing, proposed in the works of D.J. Peltier, it is necessary to update the components included in the structure of integrated marketing communications. The authors established that under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Авторами был проведен анализ определений организаций планирования в сфере маркетинга, как в отечественной, так и зарубежной профильной научной литературе, результат которого позволил выделить два принципиально разных подхода [1]. В рамках первого маркетинговая деятельность имеет четкую ориентацию на процесс, отметим, что имеются незначительные отличия в этапах, временной ориентации, а также набора компонентов, входящих в комплекс маркетинга, что неизбежным образом сказывается на специфике его работы [8]. Второй подход к организации планирования маркетинговой деятельности направлен на конечный результат, и подразумевает сбалансированное потребление ресурсов, т.е.…”
Section: литературный обзорunclassified
See 1 more Smart Citation
“…Авторами был проведен анализ определений организаций планирования в сфере маркетинга, как в отечественной, так и зарубежной профильной научной литературе, результат которого позволил выделить два принципиально разных подхода [1]. В рамках первого маркетинговая деятельность имеет четкую ориентацию на процесс, отметим, что имеются незначительные отличия в этапах, временной ориентации, а также набора компонентов, входящих в комплекс маркетинга, что неизбежным образом сказывается на специфике его работы [8]. Второй подход к организации планирования маркетинговой деятельности направлен на конечный результат, и подразумевает сбалансированное потребление ресурсов, т.е.…”
Section: литературный обзорunclassified
“…именно он сформировал и запустил изменения в непосредственном поведении потребителей, осуществил их переход на цифровые каналы [4]. Предприятия были вынуждены в кротчай-шие сроки осуществить подстройку под новую реальность, в которой маневренность, гибкость, адаптация и омниканальность оказались в числе наиболее приоритетных навыков выживания бизнеса в условиях кризиса [8]. Как правило, специалисты в области маркетинга за несколько месяцев до запуска прорабатывают рекламные компании, а в случае ребрендингов (Сбербанк Сбер, Facebook Meta и т.…”
Section: литературный обзорunclassified
“…In the course of the study, it was found that on the basis of the criterion of creating market value, it is possible to single out only four main marketing models that transform entrepreneurial structures, while each model implies the use of only the technologies and marketing mechanisms corresponding to it (Table 1). Classic models represent a different set of theoretical concepts, which over the past years have been supplemented with practical marketing approaches and methods, which means that the marketing tools/technologies used within these models in the field of organizing the transformation of entrepreneurial management structures are certainly relevant (SAZONOV, SAZONOVA, 2021). Developed by M.K.…”
Section: Literature Reviewmentioning
confidence: 99%